(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Consider two fuzzy sets A and B with same supporting points and the corresponding fuzzy vectors and respectively, where each can vary subject to the total fuzziness and each is known to us .In this paper, a comprehensive and straightforward procedure is made available to find the maximum values of some existing measures of generalized fuzzy cross entropy. Further, the continuous and piecewise convex behavior of the values so obtained is also discussed mathematically as well as graphically. Finally, a numerical example is used to illustrate the proposed method.